Tissue-Mimicking Material Fabrication and Properties for Multiparametric Ultrasound Phantoms: A Systematic Review - Jawli, Adel; Aldehani, Wadhhah; Nabi, Ghulam; Huang, Zhihong (Bioengineering (Basel), 2024)
Medical imaging has allowed for significant advancements in the field of ultrasound procedures over the years. However, each imaging modality exhibits distinct limitations that differently affect their accuracy. It is imperative to ensure the quality of each modality to identify and eliminate these limitations. To achieve this, a tissue-mimicking material (TMM) phantom is utilised for validation. This study aims to perform a systematic analysis of tissue-mimicking materials used for creating ultrasound phantoms. We reviewed 234 studies on the use of TMM phantoms in ultrasound that were published from 2013 to 2023 from two research databases. Our focus was on studies that discussed TMMs’ properties and fabrication for ultrasound, elastography, and flow phantoms. The screening process led to the selection of 16 out of 234 studies to include in the analysis. The TMM ultrasound phantoms were categorised into three groups based on the solvent used; each group offers a broad range of physical properties. The water-based material most closely aligns with the properties of ultrasound. This study provides important information about the materials used for ultrasound phantoms. We also compared these materials to real human tissues and found that PVA matches most of the human tissues the best.